The Role of Islamic Investment Objectives In Promoting Development of Muslim Societies - Dr. Hashem Osamah Yahya Mohammed; Tawfik Al-Qasemi; Al-Meqdad Al-Shami (Al-Bayan Academy for Quranic Education, 2025)
Non Indexing (Tier 4)